Comparison of outcomes of laparoscopic intracorporeal knotting technique in patients with complicated and noncomplicated acute appendicitis - Ay N; Dinç B; Alp V; Kaya S; Sevük U (Dove Medical Press, 2015)
Nurettin Ay,1 Bulent Dinç,2 Vahhac Alp,1 Şafak Kaya,3 Utkan Sevük4 1Department of General Surgery, Diyarbakir Gazi Yaşargil Training and Research Hospital, Diyarbakir, Turkey; 2Department of General Surgery, Ataturk State Hospital, Antalya, Turkey; 3Department of Infectious Disease, Diyarbakir Gazi Yaşargil Training and Research Hospital, Diyarbakir, Turkey; 4Department of Cardiovascular Surgery, Diyarbakir Gazi Yaşargil Training and Research Hospital, Diyarbakir, Turkey Background and aim: In our study we aimed to compare laparoscopic intracorporeal knotting technique (base of the appendix was ligated with 20 cm of 2.0 silk) in patients with complicated acute appendicitis (CAA) and noncomplicated acute appendicitis. Patients and methods: Ninety patients (female/male: 40/50, age ranging from 16 to 60 years, median age and interquartile range [IQR]: 25 [20; 32] years) who underwent laparoscopic appendectomy were included in the study. The patients were evaluated for the type of acute appendicitis, duration of operation, duration of hospital stay, and postoperative complications. Results: The number of cases diagnosed as CAA was 28 (31.1%), and the number of noncomplicated cases was 62 (68.9%). We found that there was no significant difference in postoperative complication rates between complicated and noncomplicated appendicitis cases. Incision site infection was seen in seven cases (7.8%) and ileus was seen in two cases (2.2%). Bleeding, intra-abdominal abscess, and appendix stump leakage were not observed in any of the cases. Median and IQR duration of operation were 42 (35; 52) minutes and median and IQR duration of hospital stay were detected as 2 (1; 2) (range 1–10) days. Conclusion: Laparoscopic intracorporeal knotting technique may be a safe, effective, and reliable technique as the materials needed for closing the appendix stumps are easily available for both CAA cases and noncomplicated cases. Keywords: laparoscopic intracorporeal knotting technique, laparoscopic appendectomy, complicated acute appendicitis